THE INFLUENCE OF KINESTHETIC PERCEPTION, HAND-EYE COORDINATION, AND SELF-CONFIDENCE ON STROKE DRIVE SKILLS IN BADMINTON GAME - Hilman Hadistya; Ramdan Pelana; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to reveal the direct and indirect effects, as well as the simultaneous effect of exogenous variables on endogenous variables. The sample in this study were 30 beginner athletes of Gold Badminton Club and Sarwendah Badminton Club Jakarta. The research approach used in this study is an associative quantitative approach, a survey method with a test technique. The data analysis technique used a path analysis approach (path analysis). Data were analyzed by path analysis through structural model testing at = 0.05. The results showed that: 1) there was a direct kinesthetic effect on the badminton game's ball drive skills of 0.438, 2) there was a direct effect of eye-hand coordination on the badminton game's ball drive skills of 0.208, 3) there was a direct influence of self-confidence on the ball drive skills badminton game is 0.336, 4) there is a direct kinesthetic effect on self-confidence which is 0.237, 5) there is a direct effect of eye-hand coordination on self-confidence which is 0.199. From the analysis of the direct and indirect effects, it can be concluded that the biggest influence is the direct effect of kinesthetic coordination on the badminton game's repulsive drive skills of 0.438.